Analisa Perilaku Konsumen terhadap Jasa Paket Perjalanan Wisata di Yogyakarta - Prihatno (Media Wisata, 2010)
Learning that there has been a great member of tourists visiting Indonesia is of course giving a big chance to have service industries especially those which have programs with package tours. Tourist as buyers of a package tour has difference conducts among each other. In marketing products, the runner of the package tour must use a customer approach strategy to be well informed about the different conducts of the customers besides other things that might attract and encourage customers to buy the package tour. The things that attract and encourage customers said above are mainly depending on the package tour that includes various tourist objects to visit and price of a package tour and availability of professional tour guides beside facilities and services to give that make the customers feel comfortable during the trip to and their presence at the tourist – object of tourism. This research is looking for reasons what tourist buy the package tour when they were to trip. Customers’ respond said that they got the trip and used a package tour because the package tour assembled by a tour wholesaler and including airfare, accommodations and activities at a set price. All the needs from the trip have included. The buyer of a package tour was the family aged fifty-one years old, a businessman and they're like with the tourist object and low price.